(untitled) (Nordic Journal of African Studies, 2003)
The paper discusses verse written in Chichewa, the national language of Malawi, that is published in Malawian newspapers, specifically the weeklies; the Weekend Nation and the Malawi News. The paper contends that the verse appearing in these newspapers are topical, essentially socio-political commentary that at the time of publication preoccupies the Malawi nation. Because the newspaper as a medium is populist the verse itself tends to be populist as well. This entails that the verse is largely ephemeral and its interest to a large extent lies not in its intrinsic quality but rather in the implications it may hold for the development of Chichewa poetry.